Left Ventricular Structure and Function in Elite Swimmers and Runners - Currie, Katharine D.; Coates, Alexandra M.; Slysz, Joshua T.; Aubry, Rachel L.; Whinton, Alanna K.; Mountjoy, Margo L.; Millar, Philip J.; Burr, Jamie F. (Frontiers in Physiology, 2018)
Sport-specific differences in the left ventricle (LV) of land-based athletes have been observed; however, comparisons to water-based athletes are sparse. The purpose of this study was to examine differences in LV structure and function in elite swimmers and runners. Sixteen elite swimmers (23 (2) years, 81% male, 69% white) and 16 age, sex, and race matched elite runners participated in the study. All athletes underwent resting echocardiography and indices of LV dimension, global LV systolic and diastolic function, and LV mechanics were determined. All results are presented as swimmers vs. runners. Early diastolic function was lower in swimmers including peak early transmitral filling velocity [76 (13) vs. 87 (11) cm·s-1, p=0.02], mean mitral annular peak early velocity [16 (2) vs. 18 (2) cm·s-1, p=0.01], and the ratio of peak early to late transmitral filling velocity [2.68 (0.59) vs. 3.29 (0.72), p=0.005]. The diastolic mechanics index of time to peak untwisting rate also occurred later in diastole in swimmers (12 (10) % diastole vs. 5 (4) % diastole, p=0.01). Cardiac output was larger in swimmers [5.8 (1.5) vs. 4.7 (1.2) L·min-1, p=0.04], which was attributed to their higher heart rates [56 (6) vs. 49 (6) bpm, p<0.001] given stroke volumes were similar between groups. All other indices of LV systolic function and dimensions were similar between groups. Our findings suggest enhanced early diastolic function in elite runners relative to swimmers, which may be attributed to faster LV untwisting.